1997
DOI: 10.1099/00221287-143-3-947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus subtilis phoR on cell wall anionic polymers

Abstract: In Bacillus subtilis the Pho regulon is controlled by a sensor and regulator protein pair, PhoR and PhoP, that respond to phosphate concentrations. To facilitate studies of the Pho regulon, a strain with an altered PhoR protein was isolated by in vitro mutagenesis. The mutation in this strain (phoR12) leads to the production of a PhoR sensor kinase that, unlike the wild-type, is functionally active in phosphate-replete conditions. The lesion in phoRl2 was shown to be a single base change that results in an Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 42 publications
2
51
0
1
Order By: Relevance
“…(1997) have shown that teichuronic acid synthesis during phosphate starvation is dependent on PhoP and PhoR, since teichuronic acid does not accumulate in either a phoP or a phoR mutant. In these mutants, the teichoic acid cell wall content does not drop to the same low level as it does in the parent strain when phosphate is depleted, suggesting that teichoic acid is the anionic polymer in cell walls of phoP and phoR mutants even when phosphate is depleted from the growth environment (Muller et al, 1997). At least part of the explanation for this phenomenon is that PhoP -P represses the synthesis of teichoic acid (Liu et al, 1998a) for these apparent differences in Pho-regulon promoter expression may be that low levels of PhoP are phosphorylated by other kinases or other phosphodonors in the phoR mutant and that the concentration of PhoP -P in the cell required for activation of Phoregulon promoters differs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…(1997) have shown that teichuronic acid synthesis during phosphate starvation is dependent on PhoP and PhoR, since teichuronic acid does not accumulate in either a phoP or a phoR mutant. In these mutants, the teichoic acid cell wall content does not drop to the same low level as it does in the parent strain when phosphate is depleted, suggesting that teichoic acid is the anionic polymer in cell walls of phoP and phoR mutants even when phosphate is depleted from the growth environment (Muller et al, 1997). At least part of the explanation for this phenomenon is that PhoP -P represses the synthesis of teichoic acid (Liu et al, 1998a) for these apparent differences in Pho-regulon promoter expression may be that low levels of PhoP are phosphorylated by other kinases or other phosphodonors in the phoR mutant and that the concentration of PhoP -P in the cell required for activation of Phoregulon promoters differs.…”
Section: Discussionmentioning
confidence: 93%
“…Several lines of evidence indicate that the genes responsible for teichuronic acid synthesis also belong to the Pho regulon and therefore are regulated by PhoP and PhoR. First, teichuronic acid synthesis is induced during phosphate starvation (Ellwood & Tempest, 1969) and secondly, a phoP and a phoR mutant are unable to synthesize teichuronic acid during phosphate starvation (Muller et al, 1997). However, how PhoP and PhoR regulate synthesis of teichuronic acid during phosphate starvation, directly or indirectly, remains unknown.…”
Section: W L I U and F M H U L E T Tmentioning
confidence: 99%
See 1 more Smart Citation
“…When the growth of B. subtilis becomes limited by the availability of phosphate, genes of the Pho regulon are either activated or repressed (24). These genes include phoA, phoB, and phoD encoding alkaline phosphatases (APases) and a phosphodiesterase-APase (13,14); the pstSACB1B2 operon encoding a high-affinity phosphate transporter (34); the tuaABCDEFGH, tagAB, and tagDEF operons involved in teichuronic acid and teichoic acid synthesis (23,25,28); glpQ encoding a glycerophosphoryl diester phosphodiesterase involved in the hydrolysis of deacylated phospholipids (2); and two genes, ydhF and ykoL, of unknown function (2,35). The members of the Pho regulon are controlled by the interaction of at least three two-component signal transduction systems (13).…”
Section: Namentioning
confidence: 99%
“…Genes of the Pho regulon that are induced in response to phosphate starvation include the following : phoA and phoB, encoding alkaline phosphatases (APases) Hulett et al, 1990) ; phoD, encoding a phosphodiesterase\APase, which has a putative role in cell-wall teichoic acid turnover (Eder et al, 1996) ; the pstSACBABB operon, encoding a highaffinity phosphate transporter (Qi et al, 1997) ; glpQ, encoding a glycerophosphoryl diester phosphodiesterase involved in the hydrolysis of deacylated phospholipids (Antelmann et al, 2000) ; the phoPR and resABCDE operons, encoding two-component signal-transduction systems PhoP-PhoR and ResD-ResE Hulett, 1996 ;Nakano et al, 2000) ; and two genes, ydhF and ykoL, of unknown function (Antelmann et al, 2000 ;Robichon et al, 2000). In addition, the expression of the tagAB and tagDEF operons, involved in the synthesis of a phosphate-containing cell-wall polymer, polyglycerolteichoic acid, is repressed (Mu$ ller et al, 1997 ;, while the expression of the tuaABCDEFGH operon, responsible for the synthesis of teichuronic acid, a non-phosphate-containing polymer that replaces teichoic acid in the wall, is induced during phosphate starvation (Mu$ ller et al, 1997 ;Lahooti & Harwood, 1999). Genes of the Pho regulon are controlled by the interaction of at least three two-component signaltransduction systems (Hulett, 1996).…”
Section: Introductionmentioning
confidence: 99%